Effects of TiO2 nanoparticle addition on the flux pinning properties of the Bi1.6Pb0.4Sr2Ca2Cu3O10+δ ceramics. Issue 14 (15th July 2022) - Pham, An T.; Tran, Dzung T.; Vu, Linh H.; Chu, Nang T.T.; Thien, Nguyen Duy; Nam, Nguyen H.; Binh, Nguyen Thanh; Tai, Luu T.; Hong, Nguyen T.M.; Long, Nguyen Thanh; Tran, Duc H.
Abstract: The effects of adding TiO2 nanoparticles on the flux pinning properties of the Bi–Pb–Sr–Ca–Cu–O (BPSCCO) system were investigated. Polycrystalline samples of (Bi1.6 Pb0.4 Sr2 Ca2 Cu3 O10+δ )1-x (TiO2 )x, where x  = 0.000, 0.002, 0.004, 0.006, 0.008, and 0.010, were fabricated by the conventional solid-state reaction method. The X-ray diffraction (XRD) results showed that all samples consisted of Bi-2223 and Bi-2212 phases. The Bi-2223 volume fraction decreased with the addition of TiO2 . Scanning electron microscopy (SEM) examination presented a degradation in texture structure with increasing misoriented grain and porosity with high doping contents. The critical temperature was decreased by TiO2 appearance in relation to Bi-2223 deceleration. Critical current density dependence on the magnetic field J c ( B ) was enhanced with x  = 0.002, 0.004 and reached maximal values on the x  = 0.002 sample. In the collective pinning theory framework, the small bundle field ( B sb ) and the large bundle field ( B lb ) were estimated, revealing the extension of the small and large bundle regimes with proper amounts of dopant. The temperature-dependent normalized critical current density ( j ) indicated that δl pinning is the dominant flux pinning mechanism in all samples. The Dew-Hughes model analyzed the pinning center properties and confirmed that TiO2 nanoparticles create normal core point pinning centers in the matrix.